Targeting food security interventions in Ethiopia: The productive safety net programme - Coll-Black, Sarah; Gilligan, Daniel O.; Hoddinott, John F.; Kumar, Neha; Taffesse, Alemayehu Seyoum; Wiseman, William (University of Pennsylvania Press, 2012)
In Ethiopia, as in many other African countries, there is a pressing need to improve household food security. An emerging consensus suggests that this is most easily accomplished through two development strategies with two complementary dimensions: investments that facilitate income generation and asset accumulation, discussed elsewhere in this book, and interventions that protect the poorest from hunger, prevent asset depletion, and provide a platform for the growth interventions. Because resources for such interventions are limited, there needs to be a mechanism for allocating these.